(untitled) (Semiárida, 2020)
Between the months of August 1985 and May 1986, 83 samples of water from different section of Santa Rosa city were analyzed to know the contens of: de NO3-, F-, SO4 2-, Cl-, CO32-,HCO3-, Na+, K+, total salt and D.T. in well water destined for human consumption. In the analyzed samples the following vas detected: - 43% of them surpases the acceptable value as regardes F- - The 8,5% of them contains an excess of NO3- - The 35% of them have a high content of SO42- - The 23% of them have surfaces the normal values of Cl- - Only 22% of them take tolerable contains of T.H., total salt and other studied ions.